Perception of English in-Service Trainees towards the use of Studentsa Mother Tongue, Afan Oromo in this Case, in EFL Classes (Global Journal of Human-Social Science, 2016)
The issue of whether the learners mother tongue should be used in the classroom has always been a subject of current debate by many researchers This paper attempts to investigate the perception of English in-service-trainees towards the use of students mother tongue Afan Oromo in this case in EFL classes The participants were 72English summer in-service trainees who came from West Arsi and Guji Zones of Oromiya region to pursue their degree program in 2016 summer program for two months at Hawassa University Data were collected through a questionnaire and semi structure interview The results indicated that EFL teachers have positive perception towards the use of Afan Oromo in their EFL classrooms The study also confirms that the use of Afan Oromo language was to explain new vocabulary especially abstract items to explain new concepts to help students develop their confidence to give instructions to raise students awareness of the differences and similarities between L1 and the target language to help students to complete pair small-group works activities to facilitate complicated English classroom tasks to help students to express their feelings and ideas when they fail to do that in English to build up a good rapport with students to explain the English idioms and expressions and to introduce new grammatical rules in order of importance
Keywords: english language; mother tongue; teachers’ perception; reasons to use l1